Captura da subjetividade: análise das políticas de gestão do trabalho utilizadas para mobilizar o engajamento dos trabalhadores de uma grande rede de supermercados. - Silva, Manuelle Cristine (2012)
This dissertation sought to investigate the management policies of the work used by a multinational supermarket chain to stimulate the engagement of workers. The aim is to understand how these policies perform what has been called the "capture" of subjectivity. In theoretical referential was possible to understand that in the capitalist system, labor relations are constructed for than the capital extract more value from workers. This holding expands on the restructuring of productive period of flexible accumulation. In this context, unemployment is shown as a great disciplinarian of the labor force and subjected workers to poor working conditions. On the other hand, companies also need the collaboration and commitment of workers, so they find ways to make them feel motivated, engaged and increase their productivity. For this purpose, they build management policies responsible for "capturing" the subjectivity of workers, aiming their greater engagement. The present study investigates the ways that capturing the subjectivity. Empirically it is based on qualitative research, conducted through a case study in a multinational supermarket business, which today operates in 18 (eighteen) states of Brazil. The study subjects were workers and managers of 06 (six) stores, located in northeastern Brazil, a total of eighteen 18 (eighteen) respondents, between managers and operators. Regarding the results of the survey found that the company has management policies responsible for "capturing" the subjectivity of workers, these policies inspired by the methods based on the production system toyotist. Among the forms responsible to capture the subjectivity, as presented by Faria and Meneghetti (2001), highlight the identity, essentiality valued collaboration for development, the productivity and total involvement, means that they can engage the worker and psychologically induced you realize what the company demands, despite the high personal cost pressures within the psychological, emotional, physical, time of life that is taken, conflicts and losses in the reconciliation of work and personal life.